Effects of sleep on multimodal cognitive functioning in college students - Xu, Yubing; Qin, Linglong; Wen, Shiman; Zhang, Xuanyu; Zhou, Yanling (Frontiers in Psychiatry, 2025)
ObjectiveWhile sleep disturbances are known to be associated with cognitive decline, the impact of sleep duration and sleep disturbances on cognitive functions remains poorly characterized in college students. This study aimed to quantify the prevalence of insomnia and poor sleep quality in a large sample of college students, and to elucidate the link between sleep disturbances and declines in different cognitive functions.MethodsThe sample consisted of 1021 college students who completed a web-based survey containing the Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), and Multimodal Cognitive Ability Self-Assessment Scale (MASQ). Data were analyzed using one-way analysis of variance (ANOVA) and generalized linear models (GLM).ResultsA total of 54.1% of college students reported insomnia, and 58.9% of the sample had poor sleep quality. Regarding sleep subgroups, shorter sleep duration was significantly associated with more severe sleep disturbances, including poor sleep quality (p<0.001), insomnia (p<0.001), difficulty falling asleep (p=0.001), daytime dysfunction (p<0.001), and Delayed Sleep-Wake Phase Disorder (DSWPD) (p<0.001). These sleep disturbances were associated with poorer cognitive performance. Furthermore, sleep disturbances, including difficulty falling asleep, difficulty staying asleep, waking up too early, daytime dysfunction, and DSWPD, were negatively associated with different cognitive functions: language, visual-perceptual ability, verbal memory, visual-spatial memory, and attention/concentration.ConclusionThe results of this study suggest that insomnia and poor sleep quality are common in college students, and short sleep duration exacerbates sleep disturbances, a combination that can lead to declines in cognitive functions.